Pengaruh Live Streaming Selling, Diskon, dan Gratis Ongkir Terhadap Impulsive Buying pada Pengguna Sunscreen Azarine dalam E-Commerce Tiktok - Dwita Rizqi Syaharani; Tika Arizona Febriani; Lasmi Yupita (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2025)
In today's digital era, marketing can be done in various ways, for example, through live streaming selling. This study aims to assess the influence of live streaming selling, discounts, and free shipping on consumers' decisions to make impulse purchases, particularly of Azarine products on TikTok E-Commerce. The approach used in this study is quantitative. The population of this study consists of TikTok e-commerce customers who have purchased Azarine products. The sample consists of TikTok e-commerce users who have purchased Azarine products during live streaming selling. A total of 52 data points were collected through an online questionnaire. Non-probability sampling was used to obtain the sample. The results of the study show that (1) live streaming selling influences 88.4% of customers' impulsive purchasing decisions. (2) Discounts can influence 98% of customers' impulsive purchasing decisions. (3) The availability of free shipping vouchers can influence 96.1% of customers' impulsive purchasing decisions.